Penguatan Kompetensi Guru dalam Pembelajaran Literasi Bahasa Indonesia Berbasis Ekonomi Syariah untuk Mendukung Profil Pelajar Pancasila - Sutarini; Mhd. Zulkifli Hasibuan; Sutikno; Maya Mut Mainnah; Tarimoi (LPPI UMN AL WASHLIYAH, 2026)
This community service activity was motivated by the suboptimal competence of teachers in integrating Islamic economic values ​​into Indonesian language literacy learning, resulting in learning still focusing on text comprehension and not fully supporting the Pancasila Student Profile. The objective of this activity was to strengthen teachers' competence in understanding and implementing contextual Islamic economic-based Indonesian language literacy learning. The implementation method used a participatory and collaborative approach through the stages of coordination, socialization, concept reinforcement, directed discussions, and evaluation and reflection. The activity was carried out in the form of material presentations, interactive discussions, and providing examples of the integration of Islamic economic values ​​in literacy learning. The results of the activity showed an increase in teachers' understanding of literacy as a contextual social practice and an increased awareness of integrating Islamic economic values ​​such as honesty, trustworthiness, and responsibility in learning. Teachers also demonstrated a positive response and initial commitment to implementing value integration in literacy activities. Thus, this activity was effective in strengthening teachers' competence and supporting meaningful learning and contributing to the formation of student character according to the Pancasila Student Profile in elementary schools.